Agricultural mechanization/motorization in Benin: Different initiatives, challenges and prospective within the period 1930-2016 - ATIDEGLA CAPO, Séraphin Cocou (My University, 2019)
Many challenges determine the strategies agricultural mechanization/motorization promotion in Benin: to enter in the world tendency through development projects; to integrate the financing or/and the promotion of agricultural mechanization/motorization in the crop production activities; to be concentrated in the reduction of work hardness and the increasing of cotton cultivated lands; increase farmers’ incomes and that of the State, to be equipped with consequent strategy. Thus, from 1930 to 2016, various initiatives of agricultural mechanization/motorization have been succeeded in Benin with as corollaries many challenges and perspectives. The study was to highlight those initiatives and to analyze their contributions to agricultural mechanization sector in Benin. Data collected in 2016 come from documentary review and some empirical knowledge of the item. It emerges from the study that many factors had negatively affected the adoption of agricultural mechanization/motorization as for consequence, a recurrent calling into question of each strategy. With regard to this situation, it is urging to reorganize the sector and reduce the effects of different constraints occurring from institutional reforms by prioritizing the financing of agricultural mechanization/motorization.
Keywords: hardness; strategy; financing; cotton cultivated land; incomes; reforms